Los modelos educativos en la educación virtual universitaria - Hidalgo Benites, Lilliam Enriqueta (2021)
The research analyzes and reflects on the contents of university educational models in order to identify the conceptions that support them, the similarities and differences in doctrinal and pedagogical philosophical approaches that animate the academic life of universities and if they respond to the requirements of virtual education that is applied today in universities across the country. To meet the objective, a documentary technique methodology is used that is based on the review of articles and books that deal with university educational models. Likewise, ten educational models from public universities in Peru were selected. As a qualitative study, categories were formulated for analysis and reflection from a content analysis file. The most important conclusion is that Peruvian public universities adopt educational foundations that revolve around humanism, which is reflected in pedagogical, curricular and didactic conceptions, focused on the development of the cognitive and attitudinal capacities of the student as protagonist and valid interlocutor in didactic communication in the classroom. However, due to the accelerated change from face-to-face to virtual education modality, it is urgent to adapt the educational models of the universities to the new educational context. Keywords: Educational model; virtual university education.